Optimizing Education Facilities in Lembang Marinding of Tana Toraja to Achieve Adaptive Education Quality - Vina Noviana, Karisma; Bahri S , Andi (Dharmahita: Journal of Community Service and Development, 2024)
This research investigates efforts to optimize educational facilities in Lembang Marinding, Tana Toraja, focusing on achieving adaptive quality education. Employing a qualitative approach with data collection through observation, interviews, and focus group discussions (FGDs), the study maps the conditions of educational facilities from early childhood education (PAUD) to high school levels and identifies existing challenges and potentials. Findings reveal issues such as inadequate library resources and insufficient technology use at the junior high school level. However, the study also highlights the potential for increased literacy, technology utilization, and interest in learning local culture among students. The research recommends improving educational facilities by restructuring libraries, incorporating technology, and integrating local cultural education. These measures are crucial for realizing adaptive quality education in Lembang Marinding. This study offers valuable insights for education stakeholders to develop strategies that align with local needs and potentials, ultimately enhancing the region's adaptive education quality.